Presencia de moluscos tropicales de la provincia panameña en la costa central del Perú y su relación con los eventos "El Niño" - Paredes, Carlos (1998)
The discovery of mollusks that normally are distributed in the boundaries of Panamanian Province in many localities of the Peruvian Province between years 1972 and 1994, period in which several events appeared "El Niño". Fifteen species of mollusks was possible determine, that extend own distribution: Pteria sterna, Orobitella peruviana, Cryptomya califórnica, Cerithium (T) stercusmuscarum, Malea ringens, Hexaplex brassica, Thais styllmanberryi, T. (M.) triangularis, T. (T.) callaoensis, Acanthina brevidentata, Purpura pansa, Neorapana muricata, Anachis (C.) nigricans, Cancellaria (C.) decussata and C. (B.) chrysostoma. Variability in the boundaries of the biogeographics provinces of the Peruvian Coast, controlled by the ENSO, has been postuled.